(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
Universities are increasingly employing part-time teachers who are experts in their field but may lack the pedagogical training crucial for teaching and assessment. Assessment, in turn, is a key factor in promoting students’ learning. Research on part-time university teachers is limited, and the assessment conceptions informing their teaching have received little attention. This study examined hourly paid teachers’ (N = 50) assessment conceptions at an open university in Finland, the relationships between these conceptions, and the differences between them by teachers’ education and teaching experience. Assessment conceptions were categorized into assessment for teaching and learning, assessment of learning, and assessment as harmful. On average, teachers’ assessment conceptions were mostly based on assessment for teaching and learning and least based on assessment as harmful. The assessment conceptions of teachers who had completed pedagogical training (60 credits) were based more on assessment for teaching and learning than the conceptions of those who had not completed pedagogical training. These results have value for the development of high-quality and sustainable university education.